Validity and reproducibility of a food frequency questionnaire to assess dietary intake of women living in Mexico City Validación y reproducibilidad de un cuestionario de frecuencia de consumo para estimar la ingesta alimentaria en mujeres de la Ciudad de México - MAURICIO HERNÁNDEZ-AVILA; ISABELLE ROMIEU; SOCORRO PARRA; JUAN HERNÁNDEZ-AVILA; HERLINDA MADRIGAL; WALTER WILLETT (Instituto Nacional de Salud Pública, 1998)
Objective. To assess the reproducibility and validity of a 116 item semi-quantitative food frequency questionnaire (FFQ), designed to assess the relation between dietary intake and chronic diseases. Material and methods. To test the reproducibility of the FFQ questionnaire, the FFQ was administered twice to 134 women residing in Mexico City at an interval of approximately one year; to assess the validity we compared results obtained by the FFQs with those obtained by four 4-day 24-hour recalls at three month intervals. Validity and reproducibility were evaluated using regression analysis and Pearson and intraclass correlation coefficients of log-e and calorie-adjusted nutrient scores. Results. Mean values for intake of most nutrients assessed by the two food frequency questionnaires were similar. However, means for the 24-hr recall were significantly lower. Intraclass correlation coefficients for nutrient intakes, assessed by questionnaires, administered one year apart, ranged from 0.38 for cholesterol to 0.54 for crude fiber. Correlation coefficients between energy-adjusted nutrient intakes, measured by diet recalls, and the first FFQ ranged from 0.12 for polyunsaturated fatty acids to 0.67 for saturated fatty acids. Regression coefficients between 24-hr recall and FFQ,s were all significant were significant for all nutrients, except for polyunsaturated fat, folic acid, vitamin E and Zinc. Conclusions. These data indicate that this semi-quantitative FFQ is reproducible and provides a useful estimate by which to categorize individuals by level of past nutrient intake. However, its application outside Mexico City or in different age and gender populations will require additional modifications and validation efforts. Objetivo. Evaluar la reproducibilidad y validez de un cuestionario semicuantitativo de frecuencia de consumo de alimentos, para ser utilizado en estudios epidemiológicos sobre enfermedades crónicas. Material y métodos. Para evaluar la reproducibilidad del cuestionario de frecuencia de consumo se comparó el resultado obtenido al aplicar la encuesta a 134 mujeres en dos tiempos separados por 12 meses. Para evaluar la validez del cuestionario, comparamos los resultados obtenidos a partir de su aplicación, con el promedio de 16 recordatorios de 24-horas, los cuales se obtuvieron en el transcurso de 12 meses. Para estimar la validez utilizamos modelos de regresión y correlación de Pearson. Para evaluar la reproducibilidad estimamos la correlacion intraclase entre los cuestionarios de frecuencia de consumo. Resultados. Las ingestas promedio diarias estimadas por los cuestionarios de frecuencia de consumo fueron similares. Sin embargo, las medias estimadas mediante los recordatorios de 24 horas fueron significativamente menores. Las correlaciones intraclase entre los cuestionarios de frecuencia de consumo aplicados 12 meses aparte, variaron entre 0.38 para colesterol y 0.54 para fibra cruda. Las correlaciones ajustadas por calorías entre el primer cuestionario y la media de los recordatorios variaron entre 0.12 para ácidos grasos polinsaturados y 0.67 para ácidos grasos saturados. En el análisis de regresión observamos asociaciones estadísticamente significativas para casi todos los nutrientes, excepto para grasas polinsaturadas, ácido folico, vitamina E y zinc. Conclusiones. Los resultados indican que el cuestionario es útil para evaluar la ingesta dietética. Sin embargo, su utilización en poblaciones con diferente estructura de edad y género o ubicación geográfica requerirá de acciones adicionales para garantizar su validez y reproducibilidad.